The thought of Jacek Kuroń from the Republican Point of View - Miksa, Joanna (Hybris, 2021)
In this paper I propose to analyze the thought of Jacek Kuroń, a prominent oppositionist during communist era and an important politician after 1989, from republican point of view. Kuroń’s thought is analyzed with the use of Hannah Arendt’s notion of public sphere and Philip Pettit’s theory of republicanism. The major themes proposed by Pettit appear in Kuroń’s thought as well, the most important of those being the citizens commitment in public life. Kuroń, as an active politician was responsible for building institutions of a liberal state after 1989, including a free market – a change that caused a dramatically high level of unemployment. In his political writings which are referred to in this paper we can find Kuroń’s comments on economical dimension of democracy and proposals of solutions to the problem of economical inequalities that are formulated in a way that might be interpreted as coherent with the philosophy of republicanism.